An approach for finite element modeling of one-dimensional thaw consolidation - R. Dayarathne; B. Hawlader; Dilan Robert (2019)
Thawing of permafrost in the North could cause many issues such as the settlement in roads, foundations, pipelines, and slope instability. For a given above-zero temperature at the boundary (e.g., at the ground surface), the excess pore water pressure generates at the thaw front that moves with time depending upon the thermal properties of the soil. The excess pore water pressure generated in the thawed soil dissipates with time, and thaw consolidation occurs. This study presents a finite element (FE) modeling technique that can simulate heat transfer, including the thawing of ice-rich frozen soil, and generation of excess pore water pressure at the thaw front and its dissipation. The FE analyses are performed for a one-dimensional condition, and the results are compared with a simplified analytical technique. The developed FE method could be used for complex boundary value problems such as thawing of frozen soil around a warm buried pipeline.